Mucoadhesive Mesalamine Prodrug Nanoassemblies to Target Intestinal Macrophages for the Treatment of Inflammatory Bowel Disease - Park, Byeongmin; Han Geonhee; Jin, Do Young; Gil kicheol; Dongwon Shin; Lee, Jong Won; Park, Jung Yeon; Jang, Hochung; Park, Daeho; Lee, Sangmin; Kim, Kwangmeyung; Yang, Yoosoo; et al. (American Chemical Society, 2024)
While mesalamine, a 5-aminosalicylic acid (5-ASA), is pivotal in the management of inflammatory bowel disease (IBD) through both step-up and top-down approaches in clinical settings, its widespread utilization is limited by low bioavailability at the desired site of action due to rapid and extensive absorption in the upper gastrointestinal (GI) tract. Addressing mesalamine’s pharmacokinetic challenges, here, we introduce nanoassemblies composed exclusively of a mesalamine prodrug that pairs 5-ASA with a mucoadhesive and cathepsin B-cleavable peptide. In an IBD model, orally administered nanoassemblies demonstrate enhanced accumulation and sustained retention in the GI tract due to their mucoadhesive properties and the epithelial enhanced permeability and retention (eEPR) effect. This retention enables the efficient uptake by intestinal pro-inflammatory macrophages expressing high cathepsin B, triggering a burst release of the 5-ASA. This cascade fosters the polarization toward an M2 macrophage phenotype, diminishes inflammatory responses, and simultaneously facilitates the delivery of active agents to adjacent epithelial cells. Therefore, the nanoassemblies show outstanding therapeutic efficacy in inhibiting local inflammation and contribute to suppressing systemic inflammation by restoring damaged intestinal barriers. Collectively, this study highlights the promising role of the prodrug nanoassemblies in enhancing targeted drug delivery, potentially broadening the use of mesalamine in managing IBD.